Association of a functional variant downstream of TNFAIP3 with systemic lupus erythematosus - Adrianto, Indra; Wen, Feng; Templeton, Amanda; Wiley, Graham; King, Jarrod B; Lessard, Christopher J; Bates, Jared S; Hu, Yanqing; Kelly, Jennifer A; Kaufman, Kenneth M; Guthridge, Joel M; Alarcón-Riquelme, Marta E; et al. (Nature genetics, 2011)
Patrick Gaffney and colleagues perform a fine-mapping study of the TNFAIP3 region in systemic lupus erythematosus using individuals from diverse ancestral populations. They identify a putative causal variant in a region of high conservation and regulatory potential that is associated with reduced TNFAIP3 expression. Systemic lupus erythematosus (SLE, MIM152700) is an autoimmune disease characterized by self-reactive antibodies resulting in systemic inflammation and organ failure. TNFAIP3 , encoding the ubiquitin-modifying enzyme A20, is an established susceptibility locus for SLE. By fine mapping and genomic re-sequencing in ethnically diverse populations, we fully characterized the TNFAIP3 risk haplotype and identified a TT>A polymorphic dinucleotide (deletion T followed by a T to A transversion) associated with SLE in subjects of European ( P = 1.58 × 10 −8 , odds ratio = 1.70) and Korean ( P = 8.33 × 10 −10 , odds ratio = 2.54) ancestry. This variant, located in a region of high conservation and regulatory potential, bound a nuclear protein complex composed of NF-κB subunits with reduced avidity. Further, compared with the non-risk haplotype, the haplotype carrying this variant resulted in reduced TNFAIP3 mRNA and A20 protein expression. These results establish this TT>A variant as the most likely functional polymorphism responsible for the association between TNFAIP3 and SLE.